Desigualdade, pobreza e governança: uma agenda para Timor-Leste - Costa, Carlos Germano Ferreira (2014)
The theme of this thesis - "INEQUALITY, POVERTY AND GOVERNANCE: AN AGENDA FOR EAST TIMOR" - stems from an interest to assess the influence of key-actors - NGOs, national governments and the United Nations System - in policy development, in developing countries that emerge from serious conflicts; in particular we search for solutions to deal with the problem of how to evaluate governance, policies and the development path in countries without reliable and structured data. This research animes to contribute to the debate on the influence of NGOs, national governments and the United Nations System on issues concerning governance, sustainable development and environment issues in developing countries that emerge from conflict featuring unconsolidated democracies; We analysed the case of East Timor, between 1999 and 2012, on issues related to social, gender and income inequality and a variety of global issues like climate change and poverty levels, based on the Millennium Development Goals (MDGs). The theoretical and methodological basis of this study was Melucci (1991). Notwithstanding this study is stakeholder-oriented based on inter- and transdisciplinary research, on multi-level and participatory governance theories and political philosophy, with focus on horizontal and environmental policy integration and processes as well as questions of legitimacy, accountability and sustainability based on the analysis of secondary sources (text, numbers, images, etc.) and collection of primary empirical data in the field, in 2012, for policy analysis in different contexts - a necessary step due to the fragility and often lack of reliable data and audited information. We analysed official documents and reports such key UN-resolutions, the Timor-Leste National Development Plan (NDP), the Millennium Development Goals Reports (MDGs), Human Development Reports (HDR), Evolution of the Human Development Index (HDI), scientific articles and several technical reports released by development agencies such as ABD, FAO, UNDP and others. We observed a huge discrepancy between rhetoric and practice concerning the key-actors participation as well as noticeable flaws in policy conduction at various levels. Transparency levels are incredibly low and it permeates all levels of the government. The impression one gets is that there was an interest in promoting the pacification process to enable foreign companies to extract oil at low risk, while issues related to governance, accountability and transparency were neglected. It is argued that such challenges were less a matter of rules and regulations then basic approaches, attitudes and power relations. It is possible that these key-actors, in general, did not succeed in find ways to change their approach during the years of stabilization; with little or no progress on issues related to human development, poverty and inequality reduction. Instead of fostering the development of a viable and autonomous civil society its results have demonstrated the depletion of a model of development that on one hand was efficient on the pacification process while on the other hand have failed in the promotion of opportunities, governance and sustainable development. Finally, we conclude that socioeconomic peculiarities and policies adopted in developing countries that emerge from serious conflicts should not be seeing as specific procedural and institutional factors replicable from stabilized societies, it is necessary to draw up a better database and a set of analysis tools based on the peculiar conditions of developing countries emerging from different forms of conflict focusing on mechanisms that promote good governance, transparency and accountability. As final considerations, to support Timor-Leste’s sustainable development policies, we point out the need to relativize the implementation of criteria considered necessary for good governance, establish a hierarchy over time and across priorities in development programs and projects, which must be guided by the specificities of particular contexts. This research contributed to the debate on the influence of NGOs, national governments and the United Nations System on issues concerning governance, sustainable development and environmental related issues in developing countries that emerge from conflict featuring unconsolidated democracies; We analysed the case of East Timor, between 1999 and 2012, on issues related to social, gender and income inequality and a variety of global issues like climate change and poverty levels, based on the Millennium Development Goals (MDGs). The theoretical and methodological basis of this study was Melucci (1992). This study is stakeholder-oriented based on inter- and transdisciplinary research, on multi-level and participatory governance theories and political philosophy, with focus on horizontal and environmental policy integration and processes as well as questions of legitimacy, accountability and sustainability. based on the analysis of secondary sources (text, numbers, images, etc.) and collection of primary empirical data in the field, in 2012, for policy analysis in different contexts - a necessary step due to the fragility and often lack of reliable data and audited information. We analysed official documents and reports such key UN-resolutions, the Timor-Leste National Development Plan (NDP), the Millennium Development Goals Reports (MDGs), Human Development Reports (HDR), Evolution of the Human Development Index (HDI), scientific articles and several technical reports released by development agencies such as ABD, FAO, UNDP and others. We observed a huge discrepancy between rhetoric and practice concerning the key-actors participation as well as noticeable flaws in policy conduction at various levels. Corruption levels are high and permeates all levels of the government. The impression one gets is that there was an interest in promoting the pacification process to enable oil companies to extract oil at low risk, while issues related to governance, accountability and transparency were neglected. It is argued that such challenges were less a matter of rules and regulations then basic approaches, attitudes and power relations. It is possible that these key-actors, in general, have not changed their approach during the years of stabilization; with little or no progress on issues related to human development, poverty and inequality reduction. Instead of fostering the development of a viable and autonomous civil society its results have demonstrated the depletion of a model of development that on one hand was efficient on the pacification procces but that on the other hand have failed in the promotion of opportunities, governance and sustainable development. Finally, we conclude that socioeconomic peculiarities and policies adopted in developing countries that emerge from serious conflicts should not be seing as specific procedural and institutional factors replicable from stabilized societies, it is necessary to draw up a better database and a set of analysis tools based on the peculiar conditions of developing countries emerging from different forms of conflict focusing on mechanisms that promote good governance, transparency and accountability. As final considerations, to support Timor-Lestes´s sustainable development policies, we point out the need to relativize the implementation of criteria considered necessary for good governance, establish a hierarchy over time and across priorities in development programs and projects, which must be guided by the specificities of particular contexts.